Persian Translation and Psychometric Properties Assessment of Self-Determination Student Scale for Adolescents - Elahe Hojati Abed; Narges Shafaroudi; Malahat Akbarfahimi; Armin Zareiyan; Akram Parand; Samaneh Karamali Esmaili (University of Social Welfare and Rehabilitation Sciences, 2019)
Objective Self-determination is the ability of recognizing, setting and achieving goals based on knowledge and self-assessment. This ability is essential for the healthy development of adolescents. Self-determination is influenced by knowledge, skills, beliefs, and contextual factors that exist in one's living environment. Since it is an essential element for having a successful life, its assessment and related skills are also important; however, there is no assessment tool for its measurement in Iranian population. The aim of this study was to translate the Self-Determination Student Scale (SSDS) into Persian and determine its psychometric properties including face, content, and construct validity as well as internal consistency and test-retest reliability in adolescents aged 14-18 years. Materials & Methods In this methodological study, the SSDS was translated into Persian to be used on Iranian population and validated according to the International Quality of Life Assessment (IQOLA) protocol. Samples were 498 high school students (mean age = 15.15±0.9; 227 females and 221 males) who were selected using convenience sampling technique with maximum diversity in Tehran. They were divided into two groups of with and without emotional/behavioral symptoms using the Youth Self-Report tool. The face validity of the translated SSDS was determined based on the opinions of samples and experts. The Content Validity Index (CVI) and Content Validity Ratio (CVR) were also calculated for each items of the translated version. The construct validity was tested by comparing known groups (gender groups and groups at risk of emotional/behavioral disorders). Moreover, its internal consistency was estimated by Kuder-Richardson formula, and test-retest reliability was tested using Intraclass Correlation Coefficient (ICC) on 16 students with a time interval of 14 days. Results In the Persian version of SDSS, 4 items were removed from the original version. After confirmation of its face validity after modification, it was found that its items had appropriate content validity based on CVI and CVR scores. The mean of self-determination score under all subscales and most of items was significant between the gender group and the group at risk of emotional/behavioral disorders (P< 0.001). The Kuder-Richardson coefficient was obtained 0.89 and for five subscales, it was in a range of 0.51 to 0.72. The ICC (0.98; 95% CI:0.95 to 0.98) approved the good reliability of the instrument. Conclusion The Persian version of SDSS had good validity (face, content, and construct) and reliability after testing it on the high school students. Therefore, it can be used in clinical and research studies to assess the self-determination of students. Considering the importance of self-definition in adolescence, there is a need for further studies using the SDSS to highlight the potential problems of high school students in self-determination and designing related training programs.